STRUKTUR, UNSUR, DAN TIPE TEKS DALAM TEKS CERITA FANTASI KARYA SISWA KELAS VII SMP NEGERI 7 PADANG - Novita, Erina; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
AbstractThis study aims to describe the structure of the text (orientation, complications, resolution), elements, and types of text contained in the  fantasy text stories written by students of class VII of  SMP Negeri 7 Padang. The data to be analyzed in the form of structure, elements, and type of text contained in the text of a fantasy story. Data collection techniques in this study were carried out through three stages. First, researchers read and understand the text of fantasy stories. Second, researchers mark the sections related to the structure of the text, elements, and types of text of fantasy stories. Third, inventorying findings related to the structure, elements, and type of text into the data inventory format Based on the results of the study, it can be concluded three things as follows. First, in general students of class VII SMP 7 Padang have used the three text structures of fantasy stories. This is evident from the 48 fantasy story texts analyzed there are 2 fantasy story texts that do not have a complete structure. Second, students generally use six elements of fantasy story text. This is evident from the 48 fantasy texts analyzed which all have complete elements, namely themes, plot, characters and characterizations, settings, points of view, and mandates. Third, the type of fantasy story text is divided into two, namely (1) based on conformity with the real world, students are more likely to write slices of fantasy stories and (2) based on story settings, students tend to write stories over time, from the present to the past. Kata Kunci: Struktur, Teks Cerita Fantasi Tipe, Unsur